2016
DOI: 10.1002/mrm.26483
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13C,15N2Urea MRI for assessment of the urea gradient in the porcine kidney

Abstract: This study demonstrates that hyperpolarized C, N -urea MRI is capable of identifying the intrarenal accumulation of urea and can differentiate acute renal functional states in multipapillary kidneys, highlighting the potential for human translation. Magn Reson Med 76:1895-1899, 2016. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…Nevertheless, both sets of results demonstrate the feasibility of obtaining approximately 1 mm isotropic resolution for hyperpolarized 13 C compounds, especially on 3T clinical scanners, as was recently demonstrated in [45]. Recent work on [ 13 C, 15 N 2 ]urea imaging on pigs at 3T [79] shows feasibility of imaging larger animals, although at a considerably coarser spatial resolution.…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, both sets of results demonstrate the feasibility of obtaining approximately 1 mm isotropic resolution for hyperpolarized 13 C compounds, especially on 3T clinical scanners, as was recently demonstrated in [45]. Recent work on [ 13 C, 15 N 2 ]urea imaging on pigs at 3T [79] shows feasibility of imaging larger animals, although at a considerably coarser spatial resolution.…”
Section: Discussionsupporting
confidence: 61%
“…In 2012, von Morze et al followed the fate of carbon‐13 labeled urea in the rat kidney, visualizing the intrarenal distribution of urea in concert with the urine concentration mechanism. These results have since then been confirmed by others in various renal disease models and been translated to the multi‐papillary kidney in pigs . In this study, we investigate the effect of glucagon on urea permeability in vivo in the rat kidney with hyperpolarized [ 13 C, 15 N]urea.…”
Section: Introductionsupporting
confidence: 60%
“…CINE‐LVF was quantified with the freely available research tool Segment version 1.9 R3697 (http://segment.heiberg.se). No RF compensation was used in this study, as B 1 has been shown previously to be adequate to image the whole abdomen with sufficient signal . Statistics were performed with one‐way analysis of variance (ANOVA), with post hoc Holm–Sidak's multiple comparisons test in Prism (GraphPad Software, Inc., La Jolla, CA, USA).…”
Section: Methodsmentioning
confidence: 99%